THE INFLUENCE OF INNOVATIVENESS, RISK TAKING, AND PROACTIVENESS TOWARD SOCIAL ENTERPRISE ECONOMIC PEFORMANCE IN SURABAYA - Lila Ramadhani Sukendy; Wendra Hartono (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2020)
This research analyzes the influence of innovativeness, risk taking and proactiveness towards social enterprise economic performance in Surabaya. The researcher uses simple random sampling method to collect the data. The data was collected by handing out questionnaires with a five-point Likert scale and there are 32 social enterprises in Surabaya who participated in this study. The data analysis process was done by using the statistical program SPSS 22. Through this research, it was found that innovativeness has a significant influence towards economic performance (sig value=0.014), whereas, risk taking (sig value=0.086) and proactiveness (sig value=0.900) do not influence economic performance significantly. Innovativeness, risk taking and proactiveness have a significant and simultaneous effect towards social enterprise economic performance in Surabaya with a significance value of 0.000. The researcher concludes that 42.8% of the change happen in economic performance can be explained by innovativeness, risk taking, and proactiveness, while 57.2% are variables that are still left to be explored. This result may vary in different sample across different country and region. Keywords: social enterprise, innovativeness, risk taking, proactiveness, and economic performance.